Analyzing the Impact of Artificial Intelligence in Big Data-Driven Marketing Tool Efficiency - Mohammad Khalaf Daoud; Maha Alkhaffaf; Marzouq Al-Qeed; Jassim Ahmad Al-Gasawneh (Migration Letters, 2023)
The rapid integration of Artificial Intelligence (AI) and Big Data into digital marketing strategies has transformed the landscape of marketing tools and their efficiency. This research, based on a sample of 300 respondents, employs Partial Least Squares (PLS) analysis to examine the impact of AI and Big Data integration on digital marketing tool efficiency. The findings reveal substantial relationships between AI integration, Big Data utilization, and tool efficiency. The study affirms a positive correlation between AI integration and marketing tool efficiency, indicating that increased AI integration leads to more efficient marketing tools. Similarly, a strong positive association is observed between the volume of Big Data utilization and marketing tool efficiency. Furthermore, the interaction between AI integration and Big Data utilization emerges as a critical moderator, significantly amplifying the impact of these technologies on tool efficiency. These results underscore the potential of AI and Big Data integration in enhancing the effectiveness of digital marketing tools. Organizations are encouraged to strategically incorporate AI and Big Data technologies to improve marketing tool efficiency, driving better customer insights and business performance. This research contributes to a deeper understanding of the dynamic interplay between AI, Big Data, and digital marketing, paving the way for more data-driven and efficient marketing strategies.